THE EDUCATIONAL OPPORTUNITIES OF TESTS WITH THE RESTORED FRAGMENTS - Oleksandr O. Petkov (Information technologies and learning tools, 2013)
The article considers the educational opportunities of the tests, which are formed by the method of the restored fragments, the analysis of the relationship tests of this type with other types of tests. It is shown the possibility of applying the tests with the restored fragments for checking the quality of learning at the level of playback: language expressions presented in text format, a set of characters that have meaning and language expressions that describe graphically displayed objects. The results of experiments that confirm the educational opportunities of the use of tests with the restored fragments to control the learning of theoretical material, education and stimulation of educational activity of students, are presented.